Immune mechanisms of acute and chronic rejection - Becker, Luis Eduardo; Morath, Christian; Süsal, Caner (Clinical biochemistry, 2016)
With the currently available immunosuppression, severe T-cell mediated rejection has become a rare event. With the introduction of modern antibody-detection techniques, such as the L-SAB technology, acute or hyperacute antibody-mediated rejection of the kidney are also seen infrequently. In contrast, chronic antibody-mediated rejection is considered to be a major contributor to graft loss in the late posttransplant phase. Problems in the management of chronic antibody-mediated rejection are effective prevention of the development of alloantibodies against donor HLA and the early identification of patients at risk for this entity. Finally, today there is still noeffective strategy to treat this indolent and slowly progressing form of antibody-mediated rejection. Herein, we review the pathomechanisms of the different forms of rejection and the clinical significance of these entities in human kidney transplantation.